Evolutionary Stability in Fiscal Competition - Andreas Wagener (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In fiscal interaction, a policy is evolutionarily stable if, once adopted by all governments, jurisdictions that deviate from it fare worse than those that stick to it. Evolutionary stability is the appropriate solution concept for models of imitative learning (policy mimicking). We show that evolutionarily stable strategies implement identical allocations, regardless of whether jurisdictions use tax rates or expenditure levels as their strategy variable. This is in contrast to the observation that the allocations in the Nash equilibria of games played in tax rates or expenditure levels differ from one another. With evolutionary play, jurisdictions set taxes and expenditures competitively, i.e., they behave as if they were all negligibly small.
Keywords: H77; C73; H72; 330